رحلة الحج عند محمد الأمين الشنقيطي: The Journey of Pilgrimage (Hajj) in the Writings of Muhammad Al-Amin Al-Shinqiti - Dr Zaib Un Nisa (Al Manhal Research Journal, 2023)
Travel literature or travelogue holds a special place in the Arab heritage. It became a rich cultural, literal, and civilizational record which reflects perceptions of travelling itself and as well as of the world. Among the most prominent journeys that combined religious depth with historical documentation, is the journey of the Mauritanian scholar Muhammad Al-Amin Al-Shinqiti in his book “The Journey of Pilgrimage (Hajj) to the Sacred House of Allah”. Al-Shinqiti dedicated a section of this work to documenting his pilgrimage to the Hijaz for the performance of the Hajj rituals. His account stands out for its integration of jurisprudential, intellectual, and religious reflections, alongside social, political, and geographical observations. His narration is not limited to describing emotions and religious sentiments; rather, it extends to analyzing general conditions in Makkah, Madinah, Dhū al-Marwah, and Dhū al-Manāsik, as well as describing the sea voyage to Jeddah, the manifestations of faith, and the networks of relationships and communication among pilgrims from all parts of the world. He also records his meeting with Prince Turki Al-Sudairi on the Day of ‘Arafah. It all makes his work a valuable source for the study of religious travel. This research, therefore, is based on a central problematic question: How did the legal, religious, and literary narrative all combine in Al-Shinqiti’s Hajj journey? The study further examines what distinguishes this journey from the writings of other Mauritanian travelers, and compares it with the travel literature of the East and the west of Arab World. The research adopts a descriptive–analytical methodology, focusing on a close reading of the text within the book “The Journey of Pilgrimage (Hajj) to the Sacred House of Allah,” highlighting Al-Shinqiti’s contribution to the development of Arabic travel literature.